Detection of Nodal Snap-through Instability in Reticulated Shell Structures Using Tilt Sensing of Members - Yan, Guirong; Li, Tiantian; Feng, Ruoqiang; Chen, Genda; Hua, Xugang; Duan, Qiuhua (Journal of Applied Nonlinear Dynamics, 2026)
Reticulated shell structures are usually built as roofs for venues where hundreds or even thousands of people assemble. Failure of this type of structure may endanger the safety of many people. This type of structure can fail due to either material failure or loss of stability (instability). Previous research on structural health monitoring has been focused on the detection of material failure. This study is to timely detect one type of instability in reticulated shell structures, nodal snap-through (NST) instability, to prevent a local NST instability from progressing into an overall structural failure. When an NST instability occurs, a joint and its connected members snap through to their new equilibrium positions, leading the geometric shape in the local area to change significantly. If the displacements at joints are able to be measured, instability can be easily detected from the deformed shape. However, it is very difficult to measure displacements for such large structures located at a high elevation, if not impossible. In this study, an approach to detecting the NST instability will be developed by identifying the change in tilting angles of members, which can be easily measured and essentially reflects the change in geometric shape caused by instability. By applying this approach, a local NST instability can be detected at an early stage, and measures can be taken to prevent a local instability from progressing into a catastrophic structural failure. The effectiveness of this approach has been validated by numerical simulations on a large-scale reticulated shell structure.